Design Features and Rationale of the BEAR-MOON (Bridge-Enhanced ACL Restoration Multicenter Orthopaedic Outcomes Network) Randomized Clinical Trial. Issue 1 (24th January 2022) - ; Spindler, Kurt P.; Imrey, Peter B.; Yalcin, Sercan; Beck, Gerald J.; Calbrese, Gary; Cox, Charles L.; Fadale, Paul D.; Farrow, Lutul; Fitch, Robert; Flanigan, David; Fleming, Braden C.; et al.
Background: BEAR (bridge-enhanced anterior cruciate ligament [ACL] restoration), a paradigm-shifting technology to heal midsubstance ACL tears, has been demonstrated to be effective in a single-center 2:1 randomized controlled trial (RCT) versus hamstring ACL reconstruction. Widespread dissemination of BEAR into clinical practice should also be informed by a multicenter RCT to demonstrate exportability and compare efficacy with bone--patellar tendon–bone (BPTB) ACL reconstruction, another clinically standard treatment. Purpose: To present the design and initial preparation of a multicenter RCT of BEAR versus BPTB ACL reconstruction (the BEAR: Multicenter Orthopaedic Outcomes Network [BEAR-MOON] trial). Design and analytic issues in planning the complex BEAR-MOON trial, involving the US National Institute of Arthritis and Musculoskeletal and Skin Diseases, the US Food and Drug Administration, the BEAR implant manufacturer, a data and safety monitoring board, and institutional review boards, can usefully inform both clinicians on the trial's strengths and limitations and future investigators on planning of complex orthopaedic studies. Study Design: Clinical trial. Methods: We describe the distinctive clinical, methodological, and operational challenges of comparing the innovative BEAR procedure with the well-established BPTB operation, and we outline the clinical motivation, experimental setting, study design, surgical challenges, rehabilitation, outcome measures, and planned analysis of the BEAR-MOON trial. Results: BEAR-MOON is a 6-center, 12-surgeon, 200-patient randomized, partially blinded, noninferiority RCT comparing BEAR with BPTB ACL reconstruction for treating first-time midsubstance ACL tears. Noninferiority of BEAR relative to BPTB will be claimed if the total score on the International Knee Documentation Committee (IKDC) subjective knee evaluation form and the knee arthrometer 30-lb (13.61-kg) side-to-side laxity difference are both within respective margins of 16 points for the IKDC and 2.5 mm for knee laxity. Conclusion: Major issues include patient selection, need for intraoperative randomization and treatment-specific postoperative physical therapy regimens (because of fundamental differences in surgical technique, initial stability construct, and healing), and choice of noninferiority margins for short-term efficacy outcomes of a novel intervention with evident short-term advantages and theoretical, but unverified, long-term benefits on other dimensions.